POLA KOMUNIKASI KELUARGA PEREMPUAN BEKERJA BERBASIS KEADILAN GENDER - Putri, Sukma Ari Ragil; Permatasari, Widya Ayu (Jurnal Komunikasi dan Kajian Media, 2024)
The construction of the human self begins with communication in the family. The communication process in the family has an important role in building family culture. A gender-fair family can start from the process of communication within the family. This study aims to see how the praxis of family communication patterns is based on gender justice from informants with different backgrounds. Using a phenomenological approach, women's experience of working in communicating with their families can be synthesized using the family communication theory of Beth A. Le Poire. The analysis criteria used used three components of family communication patterns, cohesiveness, adaptability, and communication. As a result, women's experience working in communicating with families has a clear gender justice basis when women's educational and work backgrounds are stable.